The Role of Religiosity and Father Attachment on Emotional Intelligence In Students of SMAN 1 Wonoayu - Niswah Nailan Nafisah; Zaki Nur Fahmawati (P3I UMSurabaya, 2024)
The research aims to determine whether there is a correlation between religiosity and father attachment to emotional intelligence in students at SMA Negeri 1 Wonoayu. The variables in this research are emotional intelligence as the dependent variable, while religiosity and father Attachment are independent variables. This type of research is quantitative research with a correlational approach. The population in this study was 1020 students. The sample in this study was 258 students who were determined using a stratified random sampling technique. The data collection technique used is using a psychological scale measuring instrument. Data analysis in this study used multiple regression through the SPSS version 29 computer program. The conclusion-based research conducted on students of SMA Negeri 1 Wonoayu is that there is a positive and significant influence between father attachment on the emotional intelligence of adolescent students of SMA Negeri 1 Wonoayu. Based on testing together or simultaneously (F test) amounting to,126 and significance p < 0.001.